1994
DOI: 10.1530/eje.0.1310205
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of quail oviduct phospholipase A2 activity by estradiol

Abstract: The phospholipase A2 (PLA2) activity was measured in the oviduct of immature and estradiol benzoate (EB)-treated quails. The pH profiles demonstrate the presence of two PLA2 isoforms in the avian oviduct: a neutral isoform, optimally active at pH 7-7.5 and calcium independent, responsible for most of the hydrolytic activity in the immature oviduct and poorly stimulated by estradiol; and an alkaline isoform, optimally active at pH 8-9.5 and calcium dependent, with little activity in the immature tissue but mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…This is in contrast to prior reports showing that 17␤-estradiol promotes increases in cPLA 2 protein, albeit in the quail oviduct. 32 On the other hand, in support of our findings, it was reported that prolonged exposure of ovariectomized sheep to 17␤-estradiol had no effect on cPLA 2 protein levels in the uterine artery. 33 Since cPLA 2 is involved in many cellular processes, including signaling pathways and prostaglandin and leukotriene synthesis, it is not surprising that estrogen does not specifically regulate its production in vascular tissue.…”
Section: Ospina Et Alsupporting
confidence: 88%
“…This is in contrast to prior reports showing that 17␤-estradiol promotes increases in cPLA 2 protein, albeit in the quail oviduct. 32 On the other hand, in support of our findings, it was reported that prolonged exposure of ovariectomized sheep to 17␤-estradiol had no effect on cPLA 2 protein levels in the uterine artery. 33 Since cPLA 2 is involved in many cellular processes, including signaling pathways and prostaglandin and leukotriene synthesis, it is not surprising that estrogen does not specifically regulate its production in vascular tissue.…”
Section: Ospina Et Alsupporting
confidence: 88%
“…It has been reported that E 2 has no effect on PLA 2 expression in sheep (Di et al 1999), rat (Ospina et al 2002), and baboons (Rosenthal et al 2001). In contrast, others found that estradiol or different combinations of steroid treatments promote an increase in PLA 2 protein levels (Rupnow et al 2002) and activity (Fayard et al 1994, Periwal et al 1996. These discrepancies could be due to Regulation of sPLA 2 IIA, V, and cPLA 2 at labor differences in the strains of the rats used, differences in the dose and timetable of hormones administration, as well as differences in the tissue processing.…”
Section: Discussionmentioning
confidence: 99%
“…A second extraction with 1 ml of chloroform was done and pooled chloroform extracts were evaporated to dryness under vacuum. Lipid classes were separated using anion exchange chromatography columns as described previously [22]. The iPLA 2 activity was determined from the radioactivity found in the unesterified fatty acid fraction.…”
Section: Methodsmentioning
confidence: 99%